Utilization of an environmentally-friendly monomer for an efficient and sustainable adrenaline imprinted electrochemical sensor using graphene. (1st June 2018) - Zaidi, Shabi Abbas
Abstract: Generally, the toxic and mutagenic functional monomers are employed to synthesize the MIP films. This work demonstrates the fabrication of molecular imprinted polymer (MIP) based electrochemical sensor for adrenaline using a green functional monomer, nicotinamide. The adrenaline imprinted film was electropolymerized over reduced graphene oxide (rGO) modified glassy carbon electrode (GCE) by cyclic voltammetry (CV). The as-synthesized sensors were characterized by SEM. The electrochemical analysis showed that the graphene-modified electrode exhibited excellent electrocatalytic activity toward adrenaline and the over-potential of adrenaline decreased significantly as compared to bare GCE which can be attributed to graphene's unique physical and chemical properties such as subtle electronic characteristics, attractive π–π interaction, and strong adsorptive capability of MIP film. The thickness of MIP was estimated to be 1.97 nm by coulometric analysis. This electrochemical sensor displays high selectivity owing to specific imprinted cavities for adrenaline and worked well over a wide linear concertation range of adrenaline between 0.015 μM and 40 μM with a detection limit (LOD) of 3 nM. The sensor offered good reproducibility (Relative standard deviation of 3.44%) and retained 94.6% of its initial response for over 40 days. Finally, excellent recoveries from 96.0% to 100.7% were obtained for two different samples of urine and adrenaline ampoules. Thus, this work holds great promise with numerous advantages including easy fabrication, high sensitivity and selectivity, high throughput and satisfactory reproducibility for adrenaline.